Penerapan Sustainable Development Goals dalam Bidang Kesehatan di Desa Petirhilir Kecamatan Baregbeg Kabupaten Ciamis - Yuniar Nurul Fazriyah; Regi Refian Garis; R. Rindu Garvera (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
This research was motivated by the lack of optimal sustainable development in the health sector in the village of Lightninghilir, Baregbeg subdistrict, Ciamis district. The issue of creating a healthy and prosperous society is not an easy matter, so there is a need for cooperation between the village government and each posyandu cadre in each hamlet. This research is descriptive research with a qualitative approach. The data in this research consists of primary and secondary data. The informants in this study were 7 people. Data collection techniques through literature study, interviews, field observations and documentation. Data processing or analysis techniques through data reduction, data presentation and drawing conclusions. The results of this research are: 1) Analysis of Sustainable Development Goals (SDGs) in the Health Sector in Petirhilir Village, Baregbeg District, Ciamis Regency, the results show that the strategy has been implemented but not optimally. 2) The obstacles faced are the lack of capacity of implementing cadres who carry out SDGs data collection to the community and also the public's awareness of the importance of health is still lacking, communication is not running well, the community's economy is limited, and the public is less aware of the importance of health. 3) The efforts made are that the Village Government seeks to coordinate with the community health center to prepare implementing human resources that focus on the health sector by improving environmental quality and optimizing counseling and also the duties of community development cadres and village assistants to carry out house visits.